2010
DOI: 10.1111/j.1526-4610.2009.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Disability Among Adolescents: A Student Population‐Based Study

Abstract: The Pediatric Migraine Disability Assessment provides a simple tool to measure the impact of headaches in adolescents. Adolescents with migraine headaches suffered the greatest level of disability. Higher depression scores were associated with more severe headache-related disabilities in adolescents, independent of headache frequency and severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 22 publications
9
69
1
4
Order By: Relevance
“…We too found that tiredness and stress were the most frequently reported triggers, followed by lack of sleep-probably all related; 92 % of headache sufferers said they had trouble following lessons because of these problems. Among the MH sufferers, 20 % had medium-high MIDAS scores, similarly to previous case series [15]. Nearly 90 % had never tried to obtain information on their headaches, and more than half used OTC products for pain relief.…”
Section: Discussionsupporting
confidence: 71%
“…We too found that tiredness and stress were the most frequently reported triggers, followed by lack of sleep-probably all related; 92 % of headache sufferers said they had trouble following lessons because of these problems. Among the MH sufferers, 20 % had medium-high MIDAS scores, similarly to previous case series [15]. Nearly 90 % had never tried to obtain information on their headaches, and more than half used OTC products for pain relief.…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, Pakalnis et al (30) found a significant comorbidity of migraines with signs of oppositional defiant disorder. The increased risk of depression in adults and adolescents with headaches has been well documented by several authors (6,8,(31)(32)(33)(34)(35)(36)(37), and Fuh et al (32) found association depressive disturbances and headaches to be frequent but with independent impact. In a study of young and adult patients, Antonaci et al (8) reported an increased risk of affective and anxiety disorders in patients with migraines compared to subjects without migraines, and this comorbidity was more evident in patients affected by daily chronic headaches.…”
Section: Fig 1 the Risk Analysis For Anxiety Or Depression Which Ismentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8][9][10] Publicly available data from the National Survey of Children's Health reveal that 5.3% of children aged 6 to 17 in the United States experience frequent and severe HA, including migraine. 11 Nearly three-quarters (72.8%) of these are adolescents aged 12 to 17 years, with overall prevalence of 7.5% for this age group.…”
mentioning
confidence: 99%